Kinetic modelling and reactivity of liquid nitromethane under detonation conditions - Teng Zhang; Lang Chen; Kun Yang; Bin Zhang; Tuo Yang; Yao Long; Jianying Lu; Danyang Liu; Jun Chen (Communications Chemistry)
Abstract Liquid nitromethane (NM) may undergo detonation under accidental stimuli, making kinetic modeling crucial for assessing the safety risks associated with its detonation. This study employs first-principles molecular dynamics to investigate chemical behavior of nitromethane under high temperature (>2000 K) and pressure (>1 GPa) conditions, revealing five previously unidentified intermediates (CH3NO2H, CH2NO2H, CH2NOH, CH2ONO2, NOCH2NO2) and establishing a nitromethane chemical kinetic model which include 543 elementary reactions and 79 species, which is successfully applied in the prediction of nitromethane detonation characteristics. The calculated detonation pressure (13.5 GPa) and reaction zone time (46 ns) are in agreement with the experimental values (11.5–12.0 GPa; 50–53 ns). We also uncover the delayed response mechanism in pure nitromethane detonation. The major pollutants, many CO (34.8%), and small amount of NH3 (1.7%), HCN (1.0%), etc. in nitromethane detonation products are found. These findings advance the fundamental understanding of nitromethane’s detonation reaction kinetics.